2013
DOI: 10.1002/fuce.201300070
|View full text |Cite
|
Sign up to set email alerts
|

High Molecular Weight Polybenzimidazole Membranes for High Temperature PEMFC

Abstract: High temperature operation of proton exchange membrane fuel cells under ambient pressure has been achieved by using phosphoric acid doped polybenzimidazole (PBI) membranes. To optimize the membrane and fuel cells, high performance polymers were synthesized of molecular weights from 30 to 94 kDa with good solubility in organic solvents. Membranes fabricated from the polymers were systematically characterized in terms of oxidative stability, acid doping and swelling, conductivity, mechanical strength and fuel ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 59 publications
11
117
0
Order By: Relevance
“…As seen from the figure, all membranes showed conductivities of higher than 0.01 S cm -1 and the conductivities steadily increased with the temperature up to 160 o C. However, the increase in the conductivity was almost negligible as the temperature was increased further, especially for membranes of M-1# to M-4#. As previously reported [39][40][41], the doping phosphoric acid would dehydrate at temperatures higher than 160 o C, which leads to the formation of oligomeric species of polyphosphoric acids with apparently lower conductivity than that of the orthophosphoric acid. In addition, the enhancement in the conductivity by increasing temperatures is restricted by the low ADLs of the membrane [42].…”
Section: Conductivitysupporting
confidence: 84%
See 1 more Smart Citation
“…As seen from the figure, all membranes showed conductivities of higher than 0.01 S cm -1 and the conductivities steadily increased with the temperature up to 160 o C. However, the increase in the conductivity was almost negligible as the temperature was increased further, especially for membranes of M-1# to M-4#. As previously reported [39][40][41], the doping phosphoric acid would dehydrate at temperatures higher than 160 o C, which leads to the formation of oligomeric species of polyphosphoric acids with apparently lower conductivity than that of the orthophosphoric acid. In addition, the enhancement in the conductivity by increasing temperatures is restricted by the low ADLs of the membrane [42].…”
Section: Conductivitysupporting
confidence: 84%
“…Becasue the failure of a HT-PEMFC might result from chemical and mechanical degradations of the polymer membranes, leaching of the doping acids and loss of catalyst activities [3]. As previously reported, macromolecular crosslinking [9] and increasing molecular weight [39] of the polymer could effectively improve the durability of PBI-based fuel cells. though they had the same functional group of methylimidazolium [15].…”
Section: Thermal Stabilitymentioning
confidence: 82%
“…In order to improve the mechanical strength without or with less sacrifice of the proton conductivity, various approaches have been developed. The resultful explorations include increasing molecular weight of the mPBI polymer [9,10], synthesis of PBI variants or copolymers [11][12][13][14][15][16][17][18][19], fabrication of composite membranes with nano inorganic compounds [10,20], ionically and covalently crosslinking [6,21].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal cycling stability tests showed that the open circuit voltage (OCV) degradation rate was 118% less than the pure PBI membrane. An extremely high molecular weight (from 30 to 94 kDa) PBI membrane was designed and studied by Yang et al [19]. With increased molecular weights, the PBI membrane properties including chemical stability, swelling, mechanical strength, and proton conductivity were all improved.…”
Section: Improving the Mechanical Properties And Durabilitymentioning
confidence: 99%